DEVELOPMENT OF STAGES OF THE ANTI-RECESSIONARY PROGRAM OF THE CONSTRUCTION ORGANIZATION AS BASIS STABILIZATION OF THE CONSTRUCTION SECTOR OF THE RUSSIAN ECONOMY - S. Bannova; A. Vizgalina (Вестник университета, 2019)
One of the tasks, set in the Decree of the President of 07.05.2018 № 204 “On the national purposes and strategic objectives for development of the Russian Federation until 2024” is annual improvement of living conditions. Stated purposes of the Decree of the President set to the decision for participants of an investment and construction complex of a task of adaptation to rapidly changing conditions. It is necessary to consider crisis state of many construction organizations. Performance of the Decree is possible by means of development and realization of stages of the anti-recessionary program, which main objective is concentrated in increase in efficiency use of all resources of the organizations. Stages of the anti-recessionary program for the construction organizations, which will allow define bottlenecks in their activity and to develop stabilization actions, have been developed.